Tracing out the Effects of Demographic Changes on the Income Distribution. The Case of Greater Buenos Aires 1980-2000 - Mariana Marchionni; Leonardo Gasparini (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2003)
During the last two decades fertility decisions have varied significantly and not uniformly along the income distribution. In this paper we study the effects of these demographic changes on two dimensions of the income distribution -poverty and inequality- by applying microeconometric decompositions techniques. In particular, we simulate the equivalized household income distribution that would emerge if individuals in time t took fertility decisions as in time t'. The results suggest that these demographic factors can account for a of the actual increase in poverty and inequality between 1980 y 1992.
Keywords: C25; D31; I32; J13; 330; demography; fertility; income distribution; poverty; inequality; Argentina; Greater Buenos Aires; decompositions